The impact of online marketing influencers on consumer purchase decisions - Rika Alis Handayani; Gugyh Susandy (Marketing Management Studies, 2022)
The rise of technology and information systems is increasing, creating new habits that are preferred by people today, such as finding the information necessary for personal or business interests. Social networks have evolved into an information center commonly used by the community to fill free time.The increase in internet users creates a new profession that acts as a reference information center for a particular community of content about a product and conveying the benefits of a product, then if someone is interested in looking at the content and decides to buy the product, a purchase decision is made by the consumer. Buying decisions are influenced by several factors, one of which is influencers. David Gadgetin is a content creator who actively creates content on Smartphones. The Samsung Smartphone is one of the Smartphones David often talks about on his Youtube channel. This study was conducted to determine whether Influencer Marketing has an impact on Samsung Smartphone purchase decisions at the Subang Regency Society. Deliberate sampling was used as the sampling technique, then the collected data was processed using IBM SPSS Statistics 22. The results of this study show that Influencer Marketing influences buying decisions on the Samsung Smartphone with a large influence of Influencer Marketing on buying decisions of 36.5%, while the rest is influenced by other unchecked variables.